Marconi proposes: Why it's time to rethink the birth of the BBC. Issue 3 (3rd July 2019) - Prosser, David
Abstract : New evidence requires us to revise our understanding of the birth of British broadcasting in 1922. The Post Office deployed misleading ideas about the development of commercial broadcasting in America and cemented the case for public funding and a ban on advertising. However, the idea for a single broadcaster came not from the Postmaster General but from the Marconi Company at a key meeting in May 1922 for which a transcript has emerged. It shows that ideas about public service broadcasting predate John Reith's arrival by several months. This meeting laid the foundations of broadcasting in Britain, envisaging a single broadcaster operating at arms-length from government, providing a 'public service' with national content shared between regional stations, funded by a licence fee. We can identify the exact moment the BBC was conceived. It was not the Post Office that proposed the BBC, but Godfrey Isaacs, the managing director of Marconi.